Influence of dietyl ether on the mixture of biodiesel B50 - Danang Jaya; Rico Mitchell Litaay; Ryan Ade Bagus; T.W. Widayati; Muhammad Syahri (Eksergi, 2022)
Biodiesel is generally defined as monoalkyl esters of plant oils and animal fats. Oils derived from plants and animal fats and their derivatives have the possibility as a substitute for diesel fuel. This biodiesel is then mixed with diesel with a composition of 50% biodiesel and 50% diesel to make B50. In this study, B50 was then mixed with diethyl ether. The results of this study, obtained a mixture of B50+0% diethyl ether, B50+2% diethyl ether, B50+4% diethyl ether, B50+6% diethyl ether, B50+8% diethyl ether, B50+10% diethyl ether with kinematic viscosity (6.5 mm2/s, 6 mm2/s, 5.4 mm2/s, 5 mm2/s, 4.3 mm2/s, and 3.6 mm2/s), flash point (183 oC, 179 oC, 177 oC, 175 oC, 171 oC, and 167 oC), pour point (7 oC, 6 oC, 5 oC, 4 oC, 2 oC, and 1 oC), caloric value (10051,66 cal/m3, 10097,1322 cal/gram, 10128,13 cal/gram, 10170,38 cal/gram, 10235,37 cal/gram, and 10306,84 cal/gram), and density 15 oC (841.1 Kg/m3, 839.5 Kg/m3, 838.2 Kg/m3, 837 Kg/m3, 836.2 Kg/m3, dan 835.1 Kg/m3)